USING TECHNOLOGY TO IMPROVE TEACHING AND STUDYING LITERACY - Zananda, Tiray Febria; Fadli, M Fahmi (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
A new model of technology used to improve teaching and studying literacy to arrange the class is just one way to improve the teaching and learning process. Technology, computer and internet connection will become one of the torches that can do this. It creates a fairly positive learning environment for students to learn English in an informal, stimulating, meaningful and enjoyable way with the help of audio and visual images. It combines the methods of the use of modern technology within the internet and computer programs and applied them to language instruction. With continued efforts and further improvements, technology computer and internet connection is expected to mature into a program that benefits many language learners around the world.